Adsorption of TX-100 and SDBS on the surface of alumina and maghemite nanoparticles from aqueous solutions - R. R. Mansurov; A. P. Safronov; N. V. Lakiza; D. V. Leiman (Chimica Techno Acta)
Adsorption equilibriums in aqueous aluminum and iron oxides nanosuspensions stabilized by SDBS and TX-100 were investigated using UV spectrophotometry. It was established that the non-ionic surfactant TritonX-100 is not adsorbed from aqueous solution on a hydrophilic surface of both aluminum and iron oxide nanoparticles. At the same time adsorption of the anionic surfactant SDBS was observed in both oxides nanoparticles. In the investigated range of concentrations adsorption isotherms SDBS from aqueous solution on the surfaces of nanoparticles Al2O3 and γ-Fe2O3 not reach saturation. The share of the particles surface occupied by surfactant molecules were estimated based on the value of an area of molecules SDBS in the adsorption layer, which was derived from the isotherm of surface tension (0.10 nm2). The calculations showed that at the investigated concentrations SDBS Al2O3 employed approximately 30 % of surface of nanoparticles, and for γ-Fe2O3 – up to 10%.